2007
DOI: 10.1111/j.1540-8175.2007.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Strain Imaging for Early Detection of Cardiac Involvement in Patients with Duchenne's Progressive Muscular Dystrophy

Abstract: Myocardial strain imaging in DMD patients was characterized by decreased peak systolic strain of the posterior wall despite normal standard echocardiographic findings. Strain measurement might be useful for early detection of subtle regional myocardial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 25 publications
5
43
1
Order By: Relevance
“…In the posterior wall, six of the DMD patients had postsystolic shortening in the inner-half; four of the DMD patients had systolic thinning in the outer-half of the posterior wall. These data of the current study was concordant with previous pathological and MRI studies [6,7] and tissue Doppler strain imaging studies [15,16].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the posterior wall, six of the DMD patients had postsystolic shortening in the inner-half; four of the DMD patients had systolic thinning in the outer-half of the posterior wall. These data of the current study was concordant with previous pathological and MRI studies [6,7] and tissue Doppler strain imaging studies [15,16].…”
Section: Discussionsupporting
confidence: 93%
“…The two-dimensional speckle tracking echocardiography might easily measure the strain of the myocardium with increased spatial and temporal resolution in comparison to MR tagging strain analysis. We already reported that myocardial strain imaging by tissue Doppler echocardiography is characterized by decreased peak systolic strain of the posterior wall despite normal standard echocardiographic findings [15]. However, as the derivative pitch tends to include structures outside the epicardium, the strain of the most outer portion of the posterior wall, just near the pericardium, cannot be measured.…”
Section: Discussionmentioning
confidence: 99%
“…5 There are studies showing the value of strain in identifying patients with hypertensive heart disease, 6 system sclerosis, 7 heart transplant rejection, 8 chemotherapy, 9 various cardiomyopathies and systemic muscular problems. 10 There is literature indicating the superior diagnostic value of strain vs. EF inpatients with acute heart failure. 11 A large multicenter study showed that strain assessment is both feasible and reliable in patients with LV dysfunction and allows for cardiovascular risk stratification in heart failure patients, with greater accuracy than LVEF.…”
Section: Speckle Tracking 2d Strainmentioning
confidence: 99%
“…132,148 In addition to standard 2-dimensional, Mmode, and Doppler assessments, research on strain and strain-rate echocardiographic imaging could provide future insights about disease presence and progression before detection of global dysfunction by more traditional echocardiographic indices. 144,[149][150][151][152] An important limitation in the application of standard transthoracic echocardiography in the care of patients with DMD and BMD is the diminishment of imaging (acoustic) windows because of progression of scoliosis or obesity with advancing age. 153 Thus, the use of other imaging modalities, such as cardiac magnetic resonance imaging (CMR), might better fully characterize the severity of cardiac involvement in older patients.…”
Section: Cardiac Evaluation In Dmd and Bmdmentioning
confidence: 99%